PWE-313 Epidural audit: are colorectal and surgical patients with thoracic epidurals managed appropriately?. (22nd June 2015) - Richards, ER; McNaught, C
Abstract : Introduction: Epidurals are commonly used for colorectal and general surgical patients to provide postoperative analgesia. However, they may be associated with hypotension which is often unresponsive to intravenous fluids. This audit was designed to assess the post-operative management of patients with epidurals. The standards were that epidural mediated hypotension should be recognised and managed appropriately i.e. with vasoconstrictors if required. Association of Anaesthetists of Great Britain and Ireland guidance also recommends patients with epidurals have 24 h access to clinicians experienced in epidural management. Method: A retrospective audit of consecutive patients leaving recovery with thoracic epidurals in a district general hospital. Data was collected on operation, ward, hypotension, intravenous fluids, vasopressors, anaesthetic involvement, duration of epidural anaesthesia and complications. A re-audit was conducted in 2014 after introduction of a surgical High Observations Bay (HOB). Results: Findings of the initial audit were that epidural mediated hypotension was common and was associated with repeated fluid challenges associated with significant morbidity. As a result formal teaching for surgical juniors about epidurals and hypotension was conducted, advising them to seek help and recommendations to minimise the use of epidurals and introduce a surgical high observation bay were made. The audit was then repeated. The rate of use of epidurals fell by 80% between the two audit cycles, from 24 patients in a 1 month period in June 2012 to 10 patients over a 2 month period in June 2014. There was a notable fall in their use in for elective colorectal surgical patients from 10 patients to 2 due to the adoption of alternate technique such as spinal anaesthesia or local anaesthetic wound infiltration. In the initial audit 63% of patients were managed on the ward and 37% were managed on High Dependency Unit (HDU), in the re-audit 0% of patients were managed on the ward, 55% on the surgical HOB and 44% on HDU with access to vasopressor if. Rates of hypotension fell from 63% to 30%. Excessive intravenous fluid challenges were noted in the initial audit but not the re-audit. Conclusion: This audit led to a change in practice in our institution. There has been a significant decrease in the use of epidurals, which are now reserved for high risk patients and managed on HDU or a surgical HOB with vasopressors available if necessary. The prompt involvement of senior surgical and anaesthetic staff in the care of these patients avoids excessive ineffective fluid challenges if vasopressors are required to correct the hypotension. This avoids fluid overload whilst correcting the hypotension thereby addressing concerns about anastomotic perfusion. Disclosure of interest: None Declared.